Optimizing Tuna Fish Quality through a Science-Based Sustainable Partnership Approach and Ecological Management in Boneoge Village, Central Sulawesi - Nurfadilah; Asriani Hasanuddin; Nasmia (Jurnal Penelitian Pendidikan IPA, 2024)
The potential of tuna resources is quite large, but to achieve export quality, fishermen and Fish Processing Units (UPI) must implement a strict quality assurance system, and government involvement is needed so that the tuna export process from Boneoge Village can be realized soon. This study aims to analyze partnership strategies that can be applied to improve the quality of tuna in Boneoge Village. Data collection method was carried out by purposive sampling. Basically, the data in this study were obtained and collected through triangulation (multi-method). The respondents selected in this study were ten people consisting of four fishermen, Quality Control and employees of the Fish Processing Unit (UPI), four related institutions. The data analysis used was SWOT analysis followed by QSPM analysis. Based on the SWOT analysis, there are 7 strategies that can improve the quality of partnership-based tuna in Boneoge Village, Donggala Regency. Based on the QSPM analysis, the first priority strategy is the strategy of Building Partnerships through Empowerment between the Government, UPI and Fishermen with a TAS value of 7.24, the second priority is Training in Fishermen and UPI Skills and Bureaucratic Efficiency with a TAS value of 6.27, the third priority is Improving Product Quality and Safety with a TAS value of 5.89.